The Singosari Temple Virtual Tour and Junior High School Students' Social Studies Learning Motivation: A Quasi-Experimental Study on Hindu-Buddhist Heritage Material - Meqqi Vierza; Mardhatillah Mardhatillah (Teunuleh Publisher, 2026)
When students only hear dry accounts of Hindu and Buddhist history and culture in class and do not see or connect with any media, they may lose interest and desire to learn. This study aimed to examine how a video walk of Singosari Temple affected the desire to learn in junior high school students. A quantitative quasi-experimental design with a control group that was not the same was used as the research method. The sample consisted of 64 seventh-grade students from SMPN 18 Malang. Thirty-two students from grade VII I were in the experimental group and 32 students from grade VII D were in the control group. A four-point Likert scale questionnaire that measures the desire to learn social sciences was used. It was checked for accuracy and reliability. To look at the data, we used descriptive statistics, Levene's homogeneity test, Shapiro-Wilk's normality test, and an independent-samples t-test on change scores. The motivation of the experimental group went up from M = 52.47 to M = 68.22, which is an increase of 15.75, while the motivation of the control group went up from M = 51.84 to M = 56.65, which is an increase of 4.81. The difference in scores for improvement was statistically significant (t(61) = 8.61, p <.001, d = 2.17), as shown by the t-test. The results of this study show that the video walk of Singosari Temple made students much more interested and excited about learning social sciences.